The little book of the shrinking dollar : - Wiggin, Addison (John Wiley &Sons,Inc., 2012)
Written by New York Times bestselling author Addison Wiggin, a leading economic forecaster, the book explores the reasons for the dollar's decline, and its precarious relationship to other currencies around the world. Filled with invaluable strategies for retirees, savers, and investors who want to keep their money safe no matter what lies ahead, the book is your one-stop guide to weathering the storm.